GELOMBANG PHK SEBAGAI ANCAMAN NYATA TERHADAP PENINGKATAN KEMISKINAN DAN PENGANGGURAN DI INDONESIA - Mariana, Wiwik Indra (Al-Hasyimiyah: Jurnal Ekonomi Syariah, 2025)
This study analyzes the impact of mass layoffs on poverty and unemployment in Indonesia using quantitative descriptive analysis methods with secondary data from Statistics Indonesia and the Ministry of Manpower for the period 2023-2024. Although Indonesia's open unemployment rate in February 2024 was recorded at 4.82 percent and the percentage of poor people fell from 9.03% (March 2024) to 8.57% (September 2024), the wave of mass layoffs involving 60 companies throughout 2024 has created a systemic threat to national economic stability. The research findings indicate that the impact of layoffs not only increases the potential for unemployment and structural poverty but also affects a decline in household consumption and slows economic growth through the multiplier effect. Therefore, an integrated policy strategy comprising social protection programs, skill training, and the creation of new job opportunities is necessary to address these long-term risks.